Endovascular management of six simultaneous intracranial dural arteriovenous fistulas in a single patient. (14th March 2013) - Gist, Taylor L; Rangel-Castilla, Leonardo; Krishna, Chandan; Roman, Gustavo C; Cech, David A; Diaz, Orlando
Abstract : A 64-year-old man with a history of traumatic brain injury 4 years previously presented with progressive cognitive decline and gait abnormality. MRI revealed diffusion restriction in the bilateral centrum semiovale and multiple serpiginous flow voids. Cerebral angiogram revealed a total of six intracranial dural arteriovenous fistulas with separate fistulas of the right and left sphenoid bones, left clival plexus, right transverse sinus, right sigmoid sinus, and superior sagittal sinus. A diffuse pseudophlebitic pattern of venous drainage indicating severe venous hypertension was also observed. The patient underwent a series of endovascular treatments over the next 10 months to achieve resolution of all arteriovenous shunting. Repeat MRI showed resolution of the diffusion restriction and marked reduction in T2 vascular flow voids. The patient's clinical status improved significantly over the course of treatment, paralleling the improvement in venous hypertension.